Analisis Ekonomi Produksi dan Kelayakan Finansial Usahatani Padi Berbasis Teknologi pada Skala 1 Hektar di Desa Lonrong Kecamatan Ujung Loe Kabupaten Bulukumba - Herpina, Herpina; Manusaway, Grace Stella S R; Khoirinnisa, Iin; Jamiah, Rosmiati; Islamy, Sulaiha Nor (Ekopedia: Jurnal Ilmiah Ekonomi, 2026)
Rice farming is a strategic commodity that supports food security and rural economy. This study aims to analyze the economic feasibility of rice cultivation on a 1-hectare plot in Desa Lonrong, Kecamatan Ujungloe, Kabupaten Bulukumba. The research applied a descriptive quantitative approach with 20 farmers as respondents, analyzing production costs, revenue, R/C Ratio, and Break Even Point (BEP). The results indicate that total production costs amounted to IDR 9,210,000 per hectare per cropping season, with an average revenue of IDR 28,168,000, an R/C Ratio of 4.06, and a BEP of 1,417 kg. These findings demonstrate that rice farming in Desa Lonrong is financially feasible, with significant profit margins, and that efficient use of inputs and mechanization significantly enhance profitability. The study provides guidance for optimal and sustainable local production planning.